2008
DOI: 10.1002/ejic.200700977
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Doped Zirconia Nanocrystals

Abstract: In recent theoretical work, it was predicted that transition-metal-doped zirconia (ZrO2) can be ferromagnetic at room temperature with a dependence on the metal dopant and its oxidation state and concentration.[1] For experimental verification of these predictions, manganese-doped ZrO2 nanoparticles were synthesized. The synthesis was achieved by the benzyl alcohol route, which led to high-quality nanocrystals with uniform size and shape. The obtained particles present a homogeneous distribution of the magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…When ZrO 2 is doped with metal oxides Ferromagnetic ordering was observed for both undoped and metal doped zirconia was reported by Zippel et al [41]. Paramagnetic behavior of transition metal doped zirconia was reported by Clavel et al [42]. In our case coating of ZnO over Zirconium dioxide also having the same S shaped M-H paramagnetic curve with very minute variations.…”
Section: Magnetic Studiessupporting
confidence: 66%
“…When ZrO 2 is doped with metal oxides Ferromagnetic ordering was observed for both undoped and metal doped zirconia was reported by Zippel et al [41]. Paramagnetic behavior of transition metal doped zirconia was reported by Clavel et al [42]. In our case coating of ZnO over Zirconium dioxide also having the same S shaped M-H paramagnetic curve with very minute variations.…”
Section: Magnetic Studiessupporting
confidence: 66%
“…11 However, experimental results show no clear ferromagnetic signals at room temperature. 12,13 Material quests, especially using insulators such as ZrO 2 , HfO 2 , and Al 2 O 3 , are essential for functional spin-related ceramics. Fe or Co single-ion doped HfO 2 has been reported, and slight hysteresis features mediated by oxygen vacancies were observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnetic properties of Mn-doped ZrO 2 are not fully understood. The solubility of TM ions in ZrO 2 host material is fairly low and the magnetic cluster formation is very often responsible for the observed magnetic properties [14,23,24]. No evidence of long-range ferromagnetic ordering was reported in nanoparticles of ZrO 2 doped with Mn prepared either by the coprecipitation method [23] or by the nonaqueous sol-gel approach in benzyl alcohol [14].…”
Section: Introductionmentioning
confidence: 95%
“…Pucci et al observed two types of magnetic behavior: paramagnetic behavior for pristine nanocrystals and ferromagnetic behavior due to the presence of Mn 3 O 4 phase after calcination [14]. Clavel et al reported paramagnetic behavior for nanosized ZrO 2 :Mn samples prepared by the benzyl alcohol route [24]. Paramagnetic behavior was reported for polycrystalline Y-stabilized tetragonal zirconia with up to 10% of Mn prepared by the solid state method by equilibrium [25].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation